Molly Learns a Lesson: A School Story - Tripp, Valerie (Pleasant Company Publications Incorporated, 1986)
During World War II, nine-year-old Molly goes to school and with her friends tries to aid the war effort.
Keywords: Social Issues; General; Juvenile Nonfiction